2021
DOI: 10.48550/arxiv.2101.10172
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comment on "Constraints on Low-Energy Effective Theories from Weak Cosmic Censorship"

Abstract: It was argued in the letter recently by B. Chen et. al [Phys. Rev. Lett. 126, 031102 (2021)] that the weak cosmic censorship conjecture (WCCC) can serve as a new constraint to the higher-order effective field theories. In their letter, they performed the Sorce-Wald's gedanken experiment to destroy an extremal black hole under the first-order approximation. However, after examining the calculation in their latter, we find that a key error occurs in their black hole solution. We recalculate their black hole solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, in Ref. [11], we found there exists an error in their letter. After correcting it, their discussion cannot give the constraint to the gravitational theory.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…However, in Ref. [11], we found there exists an error in their letter. After correcting it, their discussion cannot give the constraint to the gravitational theory.…”
mentioning
confidence: 82%
“…However, in Ref. [11], we reexamined their letter and found that key errors occur. After correcting the errors, their discussion cannot give the constraint to the high-order theories.…”
mentioning
confidence: 99%